Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae) - Csösz, Sándor; Radchenko, Alexander; Schulz, Andreas (Zootaxa, 2007)
The taxonomic status of 10 species of the Palaearctic Tetramorium chefketi species complex is discussed, and several nomenclatural problems are clarified. Three new species, Tetramorium exile Cs_sz & Radchenko n. sp., T. sanetrai Schulz & Cs_sz n. sp., and T. anatolicum Cs_sz & Schulz n. sp. are described. Tetramorium caespitum var. sarkissiani Forel, 1911 n. syn., Tetramorium turcomanicum Santschi, 1921 n. syn., Tetramorium taurocaucasicum Arnoldi, 1968 n. syn. are synonymized with Tetramorium chefketi Forel 1911; T. biskrensis kahenae Menozzi, 1934, n. syn. is synonymized with T. alternans Santschi, 1929; T. karakalense Dlussky & Zabelin, 1985, n. syn. is synonymized with Tetramorium sulcinode Santschi, 1927. Three taxa, T. sulcinode Santschi, 1927, T. rhodium Emery, 1922 and T. annectens Pisarski, 1969 are revived from synonymy. Lectotypes of T. chefketi Forel, 1911 and its junior synonym T. caespitum var. sarkissiani Forel, 1911, T. sulcinode Santschi, 1927, T. alternans Santschi, 1929 and its junior synonym T. biskrensis kahenae Menozzi, 1934 are designated. Gynes and males of T. sulcinode, T. annectens and T. alternans are described for the first time. An identification key to the workers and gynes of the Palaearctic species of the chefketi species complex is given. Seventy-one SEM photos and two tables with metric characters are provided for workers and gynes of all discussed species.